Study of dynamics of liquid spreading on heated surface - Chan, Han Rui (2018)
The study of droplet impact in fluid mechanics has been continuing for many years, but the exhibited behaviours of the fluid droplets are still being extensively discussed till date. The complex phenomenon of impacting fluid droplets on solid surface is experienced in many areas related to several types of cooling systems, thermal spraying, combustion engines as well as many fire safety situations. By studying the dynamic behaviour of droplet spreading upon impingement on a surface that is heated, it will further allow the author to comprehend the dynamics relationship of the physical fluid droplet with its heat transfer characteristic. The impact behaviour of ethanol droplet upon a heated surface of a glass prism was investigated using two high-speed digital cameras for side and top view imaging. The droplet impact height was varied from 10mm to 500mm and the collision dynamics were investigated with the temperature of the glass prism surface varied from 26℃ to 300℃. For each height, the evolution of the maximum spreading diameter and wetted area was measured as a function of surface temperature. A prism holder was also designed and fabricated with two slots for the insertion of two heaters to provide heating through a feedback from a thermocouple. When temperature increases above 100℃, hydrodynamic behaviours of the impacting fluids droplets, such as spreading and possibly splashing, are observed along with boiling processes, such as transition of the liquid-vapour phase, formation of bubbles on the prism surface, and droplet discharge. At a certain temperature, the Leidenfrost effect was observed.